2004
DOI: 10.1007/s00280-003-0724-7
|View full text |Cite
|
Sign up to set email alerts
|

Greater cell cycle inhibition and cytotoxicity induced by 2-deoxy-d-glucose in tumor cells treated under hypoxic vs aerobic conditions

Abstract: Overall, these results indicate that cells growing under anaerobic conditions respond with greater sensitivity to the effects of 2-DG on cell cycle inhibition and cell death than those growing under aerobic conditions. This supports our contention that glycolytic inhibitors added to standard chemotherapeutic protocols should increase treatment efficacy by selectively killing the slow-growing cells, which are found in the hypoxic portions of solid tumors, while sparing most of the normal cells that are also slo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
162
1
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 192 publications
(169 citation statements)
references
References 25 publications
3
162
1
3
Order By: Relevance
“…Based on this principle, we previously showed that 2-DG and other glycolytic inhibitors preferentially kill hypoxic as opposed to aerobic tumor cells (3 -6). However, cells growing under hypoxia were found to be more resistant to the toxic effects of this glycolytic inhibitor compared with cells in which oxidative phosphorylation has been either chemically or genetically blocked (5). This result suggested that HIF might be implicated in the mechanism of resistance to 2-DG because cells exposed to hypoxia express HIF, whereas in the latter two models where oxygen is present, HIF is not expressed (22).…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Based on this principle, we previously showed that 2-DG and other glycolytic inhibitors preferentially kill hypoxic as opposed to aerobic tumor cells (3 -6). However, cells growing under hypoxia were found to be more resistant to the toxic effects of this glycolytic inhibitor compared with cells in which oxidative phosphorylation has been either chemically or genetically blocked (5). This result suggested that HIF might be implicated in the mechanism of resistance to 2-DG because cells exposed to hypoxia express HIF, whereas in the latter two models where oxygen is present, HIF is not expressed (22).…”
Section: Discussionmentioning
confidence: 41%
“…Previously, we found that cells treated with oxidative phosphorylation inhibitors were more sensitive to the toxic effects of 2-DG compared with cells growing under hypoxia (5). A possible explanation for this increased resistance to 2-DG is that HIF is expressed under hypoxic conditions but not when cells are treated with blockers of oxidative phosphorylation in the presence of oxygen.…”
Section: Hif Expression Correlates With Reduced Sensitivity To 2-dg Imentioning
confidence: 99%
“…It has been known for decades that 2-DG, similar to glucose starvation, promotes cell cycle arrest and tumor cell death (Table 1). The effects of glucose deprivation and 2-DG are stronger under hypoxia than in normoxia, indicating that in the absence of oxygen, cells rely on anerobic glycolysis and thus become more dependent on glucose Maher et al, 2004). As tumors are frequently subjected to hypoxia, drugs that kill better under hypoxia are particularly interesting for tumor treatment.…”
Section: Glucose Deprivation and Antiglycolytics Induce Cell Cycle Armentioning
confidence: 99%
“…For instance, several glycolytic inhibitors that target key glycolytic enzymes have been tested for their anticancer activity in vitro and in vivo. [4][5][6][7][8] Such a metabolic intervention seems to produce encouraging results, at least in experimental model systems.…”
Section: Introductionmentioning
confidence: 99%